CASH FLOW STATEMENT - Pavlović, Miloš; Bogdanović, Jovan (International Journal of Economic Practice and Policy, 2013)
A cash flow is „bloodstream“ of business and without constant cash flow a company would not be able to function. The cash flow statement is statutory financial report that provides information to the interested parties on cash inflows and outflows from operating, investing and financing activities during the accounting period. This paper will discuss the origin and significance of the cash slow statement; in addition, we will define the main categories of this statement and present the methodology of its composition in accordance with IAS 7.